2022
DOI: 10.3390/jcm11144015
|View full text |Cite
|
Sign up to set email alerts
|

Does Ionized Magnesium Offer a Different Perspective Exploring the Association between Magnesemia and Targeted Cardiovascular Risk Factors?

Abstract: Evidence of the association of magnesium (Mg) with arterial stiffness has so far been conflicting. The interplay between hypertension and elevated body mass index (BMI), with hypomagnesemia, instead, has been described in the literature in a more consistent way. Our study aims at revisiting the correlations between blood Mg levels and hemodynamic and body composition parameters in the general population, exploring the sensitivity profile of ionized Mg (Ion-Mg) compared to total Mg (Tot-Mg). We collected data f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 44 publications
(75 reference statements)
0
6
0
Order By: Relevance
“…Regarding iMg, intervals of 0.53-0.67 mmol/L and 0.44-0.59 mmol/L have predominantly been utilized, while for tMg, ranges of 0.75-0.95 mmol/L, 0.70-1.00 mmol/L, and 0.70-1.10 mmol/L have commonly been used. (19) A strong positive correlation (Pearson's correlation) between iMg and tMg concentrations was found. The iMg samples were analyzed using fresh blood within 1 hour by trained research assistants in the medical ward, which may account for the observed positive correlation.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Regarding iMg, intervals of 0.53-0.67 mmol/L and 0.44-0.59 mmol/L have predominantly been utilized, while for tMg, ranges of 0.75-0.95 mmol/L, 0.70-1.00 mmol/L, and 0.70-1.10 mmol/L have commonly been used. (19) A strong positive correlation (Pearson's correlation) between iMg and tMg concentrations was found. The iMg samples were analyzed using fresh blood within 1 hour by trained research assistants in the medical ward, which may account for the observed positive correlation.…”
Section: Discussionmentioning
confidence: 86%
“…This is in concordance with the literature and supports the fact that hypomagnesemia measured by iMg is associated with unfavorable clinical outcomes, including mortality. (19,35) Besides that, the inverse correlation between serum albumin concentrations and iMg/tMg fraction can be explained by positing that individuals with lower albumin concentrations tend to have a higher proportion of their serum Mg in the ionized form. (37) This was described as "pseudohypomagnesemia" of tMg concentration as a result of hypoalbuminemia with normal serum iMg concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the fraction of iMg is not usually measured and is difficult to calculate [ 13 , 14 ]. Recent studies of various non-CKD cohorts have evidenced a moderate correlation between tMg and iMg [ 15 , 16 ]. Given the variations and/or impairments in serum binding proteins observed in patients with CKD, one could expect to find the same moderate correlation in this population.…”
Section: Introductionmentioning
confidence: 99%
“…The association between magnesium levels and CV outcomes has not been frequently evaluated, and the few published data are conflicting [ 22 , 23 , 25 , 28 ]. Furthermore, most studies of the link between magnesium and patient outcomes have focused on tMg concentrations and not iMg, and some studies have reported that tMg and iMg are not related in the same way to the predicted clinical outcomes [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Literature data suggested a correlation between serum magnesium levels in the upper part of the distribution and lower arterial stiffness parameters [ 5 ]. However, most recent findings suggest that ionized magnesium should be used as a more specific marker of the magnesium status indicating its association with arterial stiffness [ 6 ].…”
mentioning
confidence: 99%